FACTORS INFLUENCING ADOLESCENT EATING HABITS DURING THE NEW NORMAL ERA OF THE COVID-19 PANDEMIC IN DENPASAR CITY - Satiawati Kurnianingsih, I Desak Ketut Dewi; Batiari, Ni Made Padma; Oktavianti, Ni Kadek Rika (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
The study aims to comprehend how the eating habits of school adolescents have changed during the adaptation period of the new normal of COVID-19, as well as to evaluate the relationship between adolescents' sociodemographic characteristics and learning methods in school with their eating habits. A cross-sectional quantitative study was conducted in Denpasar City with 352 adolescents aged 10-21 years, utilizing a questionnaire measuring eating habits based on the Adolescent Food Habits Checklist (AFHC). The research results indicate that factors such as age (OR=7.57; p<0.05), gender (OR=0.39; p<0.05), parental income (OR=1.83; p<0.05), and learning methods (OR=2.71; p<0.05) in school influence adolescent eating habits. Furthermore, the majority of adolescents (60%) exhibit poor eating habits, with a significant portion having suboptimal nutritional status, including 46.3% underweight, 11.1% at risk of overweight, and 3.4% classified as Obesity II. Therefore, collaboration among parents, schools, and health departments is essential to promote healthier eating patterns for adolescents.